Application of support vector machine in a traffic lights control - Całuch, Artur; Cieślikowski, Adam; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2020)
This article presents the process of adapting support vector machine model’s parameters used for studying the effect of traffic light cycle length parameter’s value on traffic quality. The survey is carried out using data collected during running simulations in author’s traffic simulator. The article shows results of searching for optimum traffic light cycle length parameter’s value.